The Analysis of Shuttlecock Velocity Based on the Field Test Method of The Home Industry Products in Indonesia - Yusup, Ucup; Rusdiana, Agus (Universitas Pendidikan Indonesia, 2020)
One of the main components of badminton games is shuttlecock. The shuttlecock home industries in Indonesia mainly employ for about 20-40 freelance workers. The workers in the home industries are able to produce 500-100 slops of shuttlecock daily. The guarantee of the shuttlecock quality produced by home industries, either through the laboratory tests or field tests, is rarely conducted formally. Therefore, we are interested in conducting an academic study on the velocity of the shuttlecocks produced by the workers of the shuttlecock home industries that have been distributed in Indonesia markets. There are eight widely distributed shuttlecock brands produced by the home industries in Indonesia, including Taiso, Saporate, Netra, Arjuna, Kuda Mas, Rivals, Purnama, and Spin. The purpose of this study was to examine the quality of aerodynamics rate of the shuttlecock produced by home industries by comparing the rate of motion of the shuttlecock in different distances started from the initial velocity to the final velocity when the shuttlecocks impact to the ground. The method used in this study was a descriptive qualitative study. The instruments used were three high resolution handy cams, a set of calibration, and the 3D motion analysis system software (Frame Diaz IV). The result of this study showed that the average velocity of the shuttlecock, started from the initial velocity to the final velocity with 5 meter distance, reached 85.0 m/s., while the average final velocity reached 29.8m/s at 5 meter distance. From all of the shuttlecock types tested in the field test for their velocity, it was found that the Spin brand moved with a high velocity with 12.8% of percentage. Meanwhile, the lowest velocity of the shuttlecock was found in the Taiso brand where the percentage was 15.3% in 9 meter and12 meter distances. The study concludes that the average of various shuttlecock brands’ speeds are in the normal category except for the Taiso and Spin brands.